Noise immunity of active vibro-acoustic method of monitoring the state of the main pipeline - A. A. Fedotov; R. A. Ahmedzhanov (Омский научный вестник)
Improving noise immunity is one of the main tasks in developing methods and systems of vibro-acoustic control. The simulation of the functioning of the active vibro-acoustic method of monitoring the state of the main pipeline is implemented using the analytical model of transverse vibrations of the rod with the addition of interference received on the operating pipeline. The results give grounds for drawing conclusions about the prospects of using coherent signal accumulation in active pipelines monitoring systems.